Foreign experience of formation of national digital infrastructure on social research (Journal of Economic Research & Business Administration, 2020)
This article is devoted to study foreign experience of formation of national digital infrastructure onsocial research. The object of the study is the national digital infrastructure on social research in GreatBritain and the countries of the European Union, the subject is the organizational and economic relationsthat are developing in the process of their formation and functioning. The study was conductedon the basis of a system-structural and functional approach using generalization, systematization andinduction methods. The information base of the study are the roadmaps for the formation and developmentof digital research infrastructure in the UK and European Union countries. During the study,there were identified the tendencies in social sciences development in the context of digitalization,there was shown the variety of digital research infrastructures in the field of the humanities and socialsciences, there were analyzed the digital infrastructure on social research at the country and regionlevels, there were identified the factors affecting on formation and development of national digitalinfrastructure on social research. The findings of study results can be used to determine the prioritydirections for the development of the Kazakhstan’s national model of digital infrastructure on socialresearch.